2021
DOI: 10.1002/pi.6189
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance hybrid luminescent‐scattering solar concentrators based on a luminescent conjugated polymer

Abstract: Luminescent solar concentrators (LSCs) are considered a promising building‐integrated photovoltaic technology. Over the past decade, numerous luminophores have been developed for LSCs. However, conjugated polymers are rarely reported for LSCs despite their wide application in other fields. In this study, we investigated a luminescent conjugated polymer, poly(naphthalene‐alt‐vinylene) (PNV), for LSCs. PNV exhibits an absorption wavelength (λabs) of 535 nm, an emission wavelength (λem) of 632 nm and a photolumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 84 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…To date, numerous studies on the LSCs have focused on developing novel luminescent materials [24][25][26] and optical techniques [27][28][29][30] to enhance the performance of LSCs. However, only a handful of reports demonstrated devices with power conversion efficiencies (PCEs) (>5%) and/or high concentration ratios (>2) at large scales [31][32][33][34][35]. According to a theoretical study, LSCs are subjected to over 50% photon loss due to the luminophore self-absorption, host matrix absorption, and waveguide escape [36].…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous studies on the LSCs have focused on developing novel luminescent materials [24][25][26] and optical techniques [27][28][29][30] to enhance the performance of LSCs. However, only a handful of reports demonstrated devices with power conversion efficiencies (PCEs) (>5%) and/or high concentration ratios (>2) at large scales [31][32][33][34][35]. According to a theoretical study, LSCs are subjected to over 50% photon loss due to the luminophore self-absorption, host matrix absorption, and waveguide escape [36].…”
Section: Introductionmentioning
confidence: 99%
“…[344] Several research works presented semitransparent colored LSC based on QDs and conjugated polymers, for coupling with PV. [91,[345][346][347][348][349] Internal Design Strategies: The thickness of the transparent electrodes can be adjusted to achieve colorful semitransparent SCs. Jiang et al showed that changing the thickness of a PEDOT:PSS electrode between 48 and 160 nm allowed a wide range of color in semitransparent PSC (Figure 7c).…”
Section: Semitransparent Colored Solar Cell Technologiesmentioning
confidence: 99%
“…[ 344 ] Several research works presented semitransparent colored LSC based on QDs and conjugated polymers, for coupling with PV. [ 91,345–349 ]…”
Section: State Of the Art Of Tunable Solar Cell Technologiesmentioning
confidence: 99%
“…An LSC with the dimensions of 6 in × 6 in × 1/4 in (152.4 mm × 152.4 mm × 6.35 mm) was fabricated in this study. The fabrication procedure was according to a previous report [32], where a thin (thickness: approximately 15 µm; density: 1.18 g cm −3 ) polymer (poly(methyl methacrylate) (PMMA)) layer containing perovskite (CsPbI 3 ) NCs was sandwiched between two clear acrylic sheets, and four gallium arsenide (GaAs) solar cells connected in parallel were used to attach to the waveguide. Liquid optically clear adhesives (refractive index: 1.52@590 nm; cure by heating at 50 • C for 1 day) were used for index matching between the solar cells and the waveguide.…”
Section: Experimental 21 Device Fabricationmentioning
confidence: 99%